Mapping universities-communities partnerships in the delivery of the Sustainable Development Goals - Leal Filho, Walter; Dibbern, Thais; Viera Trevisan, Laís; Coggo Cristofoletti, Evandro; Dinis, Maria Alzira Pimenta; Matandirotya, Newton; Sierra, Javier; Shulla, Kalterina; Buttriss, Gary; L’Espoir Decosta, Patrick; Mbah, Marcellus Forh; Sanni, Maruf (Frontiers in Environmental Science, 2023)
The establishment of partnerships between universities and communities can significantly support the implementation of initiatives related to sustainability as a whole and help to realize some of the United Nations (UN) Sustainable Development Goals (SDGs). Despite the usefulness of mapping of partnerships, there is a perceived necessity for studies, which may shed some light on these interactions, and the many advantages they offer. Against this background, this paper reports on a study which has assessed the extent to which partnerships between universities and communities may assist in achieving the SDGs. Methodologically, by means of a bibliometric analysis and the use of a set of enlightening case studies, the paper introduces some of the partnerships being implemented today and draws the lessons learned, which may be helpful in future initiatives. A total of eight initiatives are presented and discussed during the paper. The results suggest that more joint efforts are needed, as part of efforts to accelerate the implementation of the SDGs at the university level, including a list of measures that Higher Education Institutions (HEIs) could apply to address those goals. Overall, this research contributes to the sustainability area by providing empirical evidence, insights, and recommendations for fostering partnerships between universities and communities. It adds to the existing body of knowledge and understanding of how collaborative efforts can contribute to sustainable development and the achievement of the SDGs.